Auditory Hallucinations Elicit Similar Brain Activation in Psychotic and Nonpsychotic Individuals - Diederen, Kelly M. J. (Oxford University Press, 2012)
While auditory verbal hallucinations (AVH) are most characteristic for schizophrenia, they also occur in nonpsychotic individuals in the absence of a psychiatric or neurological disorder and in the absence of substance abuse. At present, it is unclear if AVH in these nonpsychotic individuals constitute the same phenomenon as AVH in psychotic patients. Comparing brain activation during AVH between nonpsychotic and psychotic individuals could provide important clues regarding this question. 21 nonpsychotic subjects with AVH and 21 matched psychotic patients indicated the presence of AVH during 3T functional magnetic resonance imaging (fMRI) scanning. To identify common areas of activation during the experience of AVH in both groups, a conjunction analysis was performed. In addition, a 2-sample t-test was employed to discover possible differences in AVH-related activation between the groups. Several common areas of activation were observed for the psychotic and nonpsychotic subjects during the experience of AVH, consisting of the bilateral inferior frontal gyri, insula, superior temporal gyri, supramarginal gyri and postcentral gyri, left precentral gyrus, inferior parietal lobule, superior temporal pole, and right cerebellum. No significant differences in AVH-related brain activation were present between the groups. The presence of multiple common areas of AVH-related activation in psychotic and nonpsychotic individuals, in the absence of significant differences, implicates the involvement of the same cortical network in the experience of AVH in both groups.